Modulating the gel properties of soy glycinin by crosslinking with tyrosinase. (September 2016) - Isaschar-Ovdat, Sivan; Davidovich-Pinhas, Maya; Fishman, Ayelet
Abstract: The gelation progression and gel properties of enzymatically crosslinked soy glycinin were evaluated in comparison to non-crosslinked glycinin. Glycinin was initially crosslinked using tyrosinase from Bacillus megaterium (TyrBm) and was later used to form gel upon heating. Gelation was evaluated by small deformation rheological measurements and revealed a significant increase in storage modulus (G′) obtained in the crosslinked gel. This was confirmed by temperature sweep and frequency sweep measurements that supported the results and proved that the difference in modulus was not frequency dependent. Texture profile analysis showed an increase in hardness and decrease in elasticity of the crosslinked gels. Scanning electron microscopy (SEM) images displayed a more structural network with larger pore size in the crosslinked gel. The less dense structure of the crosslinked glycinin gel network led to a slight decrease in the water holding capacity. Finally, thermal analysis using differential scanning calorimetry (DSC) confirmed no change in the gelation point induced by denaturation, however thermal gravimetric analysis (TGA) did show a difference in the decomposition profile of the crosslinked protein compared with non-crosslinked glycinin. The results suggest that by applying TyrBm mediated crosslinking we may modulate the protein gel properties for tailoring the texture of food products. Graphical abstract: Highlights: Tyrosinase from Bacillus megaterium (TyrBm) was used as a biological crosslinker of soy glycinin. The TyrBm-crosslinked protein gels were firmer and less elastic than non-crosslinked glycinin gels. TyrBm-crosslinked gel presented a modified, more organized gel network. The crosslinked glycinin gel comprised larger pores, which decrease the WHC of the gel while increasing the potential of encapsulation.